Formulasi Dan Uji Stabilitas Fisik Lip Balm Alami Berbahan Dasar Cera Flava Untuk Perlindungan Bibir Pada Praktikum Farmasetika - Dea Lestari; Amraini Amelia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Lip balm is a cosmetic product designed to protect and maintain the moisture of the lips, especially from environmental factors that can cause dry, cracked, or irritated lips, such as low temperatures and wind. Dry lips can interfere with comfort and appearance, making protection with lip balm essential. This study aims to formulate and evaluate a lip balm preparation made from a combination of natural and chemical ingredients, such as cera flava, oleum cacao, nipagin, glycerin, lanolin, and the addition of powder dye. These ingredients were chosen because of their ability to maintain lip moisture, provide protection against external factors, and ensure long-term safety for use. The lip balm manufacturing process begins with heating the primary ingredients, cera flava and oleum cacao, which are melted first. After the primary ingredients have melted, additional ingredients such as nipagin, glycerin, lanolin, and powder dye are added gradually. The mixture is stirred carefully to ensure that all ingredients are evenly blended. Once all the ingredients are well-mixed, the liquid mixture is poured into molds and allowed to cool and harden. This process is crucial for achieving the desired lip balm texture, which should not be too hard or too soft and should facilitate easy application to the lips. Based on the analysis results, the formulated lip balm demonstrates good physical stability, without significant changes in color, odor, or texture during testing. The lip balm also provides ease of use, with a smooth texture that is easy to apply to the lips. The results of this study show that the combination of ingredients used can produce an effective lip balm product that maintains lip moisture and provides optimal protection against harsh environmental conditions, such as low temperatures.